The Role of Mobile Money in Mitigating Financial Exclusion in Rural Zimbabwe: An Empirical Study - Kudakwashe Munyepwa; Charity Ranganayi; Norah Gwesu; Liberty Mudzengerere; Mandongwe Lucia; Pauline Machaka (International Journal of Financial, Accounting, and Management, 2026)
Purpose: This study investigates the role of mobile money services in enhancing financial inclusion in rural Zimbabwe by addressing the barriers of traditional banking systems. Research Methodology: A mixed-methods approach was adopted, combining household surveys for quantitative data on mobile money usage with key informant interviews from mobile agents and local leaders for qualitative insights. Secondary data from institutions such as the Reserve Bank of Zimbabwe and POTRAZ provided context. Quantitative data were analyzed using SPSS, and thematic analysis was employed for qualitative responses. Results: The findings indicate that mobile money services, notably EcoCash, OneMoney, and TeleCash, significantly impact financial participation by reducing transaction costs and overcoming geographical barriers. Users benefit from improved access to savings, remittances, and microcredit, especially women and youth. Conclusions: Although mobile money addresses some aspects of financial exclusion, it is not a panacea. Challenges, such as limited network coverage and low digital literacy, persist, restricting their potential. Limitations: The study's focus on selected rural districts may not represent the entire country, and variations in participants' financial literacy could influence the survey results. Contributions: This research offers evidence-based insights for policymakers and stakeholders, emphasizing mobile money's potential to foster inclusive economic growth, mitigate poverty, and enhance financial access in developing economies.